Analisis Keseimbangan Kehidupan Kerja, Stres Kerja dan Lingkungan Kerja Pengaruhnya terhadap Kinerja Karyawan pada PT Multicentral Aryaguna - Dita Rahmanita; Jayadi Jayadi; Mursida Kusuma Wardani; Meli Andriyani (Jurnal Syntax Admiration, 2025)
This research was conducted with the aim of determining the influence of work-life balance, work stress and work environment on employee performance at PT Multicentral Aryaguna. This research was conducted at PT Multicentral Aryaguna. The population in this study were 165 employees of PT Multicentral Aryaguna. The number of samples taken in this study used the Slovin formula technique with an error rate of 10% which resulted in 63 and rounded up to 65 respondents. The data taken from this research was obtained directly using a closed questionnaire. The multiple regression analysis tool was calculated with the help of the SPSS version 16 program. The results of the research were obtained using the t test and F test. The research instrument was carried out through validity and reliability tests. The research produced three main findings in accordance with the proposed hypothesis, namely: 1) Work Life Balance has a positive and significant influence on Employee Performance. 2) Job Stress has a negative and significant influence on Employee Performance. 3) The work environment has a positive and significant influence on employee performance.